STUDI PENGARUH PENAMBAHAN SERABUT NANGKA (Artocarpus heterophyllus) TERHADAP KUALITAS FRUIT LEATHER BUAH NANAS (Ananas comosus L. Merr) - Nur, Siti Sabahan; Ralle, Andi; Alimuddin, Suraedah; Fitri, Besse Yunita Safika (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 10 No 2 (2023): Scientific Journal of Food Technology (September)DO - 10.24843/MITP.2023.v10.i02.p75-85, 2024)
Fruits have good market prospects apart from being eaten fresh and fruit leather snack food products. This product is quite interesting to be developed commercially in Indonesia. The aim of the study was to analyze the effect of adding jackfruit fiber puree on the quality of pineapple fruit leather. The study was arranged in a completely randomized design (CRD) with the following treatments: 100% pineapple puree, 85% pineapple puree + 15% jackfruit puree, 75 pineapple puree + 25% jackfruit puree, 65% pineapple puree + 35% puree jackfruit fiber, and 55% pineapple puree + 45% jackfruit fiber puree. Each treatment was added 150 g of sugar, 10 g of Arabic gum, and 2 g of citric acid. The results of the study showed that the addition of jackfruit fiber had a good effect on the quality of pineapple fruit leather. The composition of 55% pineapple puree plus 45% jackfruit fiber puree resulted in an ash content of 1.49%, a moisture content of 13.72%, a fiber content of 26.07%, and the panelist's level of preference for color, aroma, taste 3.0-4.0 (rather like to like) and a bit chewy texture.